Clinical Experience with Major Hepatic Resections in Ramathibodi Hospital - Wilasrusmee, Chumpon; Chuphongphairot, Monchai; Kanchanapanchaphol, Siroj (The Thai Journal of Surgery, 1998)
During 5 years and 10 months period from January 1, 1992 to October 31, 1997, 118 major hepatic resections were performed and 96 medical records were available for retrospective review. There were 63 males and 33 females. Age ranged from 25 to 84 years (average 53.73 years). Indications for surgery were 43 hepatocellular carcinomas,36 cholangiocarcinomas, 10 metastatic cancers, 2 sarcomas and 5 benign lesions. Among 96 operations, there were 43 right lobectomies, 34 left lobectomies, 3 right trisegmentectomies, 9 left lateral segmentectomies, and 7 other segmentectomies. There were 54 operative complications from 29 patients (30.2%). Operative mortality was 8.3% (8 mortality cases). Overall 1 and 3 years survival was 71.05% and 52.93% respectively. The mean survival was 3.25 years. The morbidity, mortality, and long term survival of major hepatic resection in Ramathibodi hospital were comparable to other reported series.